Identification of Vibrio metschnikovii and Vibrio injensis Isolated from Leachate Ponds: Characterization of Their Antibiotic Resistance and Virulence-Associated Genes - Aura Falco; Miguel Ángel Villaquirán-Muriel; José David Gallo Pérez; Alejandra Mondragón-Quiguanas; Carlos Aranaga; Adriana Correa (MDPI AG, 2023)
This study aimed to evaluate the antibiotic resistance of 22 environmental Vibrio metschnikovii isolates and 1 Vibrio injensis isolate from landfill leachates in southwestern Colombia. Isolates were identified by Matrix-Assisted Laser Desorption/Ionization-Time-Of-Flight (MALDI-TOF), and 16S ribosomal RNA gene sequencing. Analysis of the susceptibility to six antibacterial agents by the Kirby-Bauer method showed susceptibility of all the isolates to ciprofloxacin and imipenem. We recorded resistance to beta-lactams and aminoglycosides, but no multidrug resistance was observed. The genome of one of the isolates was sequenced to determine the pathogenic potential of V. injensis. Genes associated with virulence were identified, including for flagellar synthesis, biofilm formation, and hemolysins, among others. These results demonstrate that landfill leachates are potential reservoirs of antibiotic-resistant and pathogenic bacteria and highlight the importance of monitoring Vibrio species in different aquatic environments.